PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN FASHION MUSLIMAH (Studi kasus pada Suna Gallery Banjarmasin) - Fatimah, Mita; Syamsuddinnor, Syamsuddinnor; Alfiannor, Alfiannor (CV. Anugerah Duta Perdana, 2023)
The aim of this research is to determine whether the Marketing Mix, comprising Product, Price, Place, and Promotion, has an influence on the purchase decisions of Muslimah products at Suna Gallery Banjarmasin, both partially and simultaneously. The general population in this study consists of customers making purchasing decisions at Suna Gallery, while the target population for this research is customers who made purchases during the period from January to December 2022. The research sample was selected using the Purposive sampling technique, and with the Slovin formula, a sample size of 84 individuals was determined. The analysis method in this research employs the Likert Scale for research questionnaires, data processing with SPSS version 25.0, data presentation using tables, and statistical data analysis using classic assumption test analysis methods, multiple regression analysis, coefficient of determination, and hypothesis testing. Based on the results of this research, it is evident that product, place, and promotion have an influence on purchase decisions at Suna Gallery. However, the price variable does not significantly affect purchase decisions. Simultaneously, the Marketing Mix has an influence on the purchase decisions of Muslimah fashion products at Suna Gallery Banjarmasin